1988
DOI: 10.1136/bjo.72.9.660
|View full text |Cite
|
Sign up to set email alerts
|

Reflow of obstructed capillaries in the maculae of humans with diabetic retinopathy, observed by fluorescein angiography.

Abstract: SUMMARY As diabetic retinopathy progresses, the non-perfused area in the retina gradually enlarges as the capillaries are obstructed. To elucidate the process of capillary obstruction we examined macular capillaries in 104 diabetics, using fluorescein angiography. The follow-up period was three to eight years. We found that some capillaries in the macula were obstructed, then became unobstructed. Reflow of blood into the macula after the obstruction was observed in nine patients (8.7%). The time between obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
(2 reference statements)
1
11
0
Order By: Relevance
“…As some previous studies showed that early retinal capillary closure might be transient and reversible the strict control seems to be crucial to prevent the loss of vision in youths with T1D. [ 36 ] The main limitation of the study is poor representativeness of the sample–all subjects were Caucasian, majority of them came from the central part of Poland, and the lack of differences in this clinical population may not reflect the entire cohort of T1D children across the world.…”
Section: Discussionmentioning
confidence: 99%
“…As some previous studies showed that early retinal capillary closure might be transient and reversible the strict control seems to be crucial to prevent the loss of vision in youths with T1D. [ 36 ] The main limitation of the study is poor representativeness of the sample–all subjects were Caucasian, majority of them came from the central part of Poland, and the lack of differences in this clinical population may not reflect the entire cohort of T1D children across the world.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic diabetic retinal vascular occlusion, resulting from activated granulocytes and monocytes (24), is reversible and reperfusion has been documented angiographically in diabetic eyes (25). Elevated levels of ROI reaction products have been directly correlated with neovascularization in human (26) and rat (27) diabetic eyes, and in eyes with retinopathy of prematurity (28).…”
Section: Introductionmentioning
confidence: 99%
“…It might therefore represent the last reversible stage before further deterioration into irreversible and complete non-perfusion. Yamana et al have shown that some capillaries in the macula were obstructed and then became unobstructed in 8.7% of the diabetic patients whom they followed [12].…”
Section: Discussionmentioning
confidence: 96%